Kreativitas Guru dalam Meningkatkan Minat Belajar Siswa pada Mata Pelajaran Matematika di MI Tarbiyyatul Arifin - Rahma, Mia; Irawan, Wahyu Henky; Abdussakir, Abdussakir (Indo-MathEdu Intellectuals Journal, 2024)
Education is a component that is used as a reference for the progress of a nation. This research aims to examine teachers' creativity in learning mathematics to increase students' interest in learning. A teacher must have great creativity in the learning process so that students can be interested in learning mathematics. This research is qualitative that took place in MI Tarbiyyatul Arifin. Data collection was carried out through structured interviews, observation and documentation. Data analysis is carried out by collecting data, presenting it and drawing conclusions. The results of the research show that the creativity that an educator possesses is product creativity and person creativity. Product creativity in the mathematics learning process uses media in concrete ways that use real-life examples. The personal creativity that an educator possesses is that he or she has a good personality, is intelligent, has new ideas in the learning process, is friendly, is good at communicating and can dominate the class well. The learning process can also be enjoyable and comfortable for students to learn. This increases the interest of MI Tarbiyyatul Arifin students in learning